Case Report: Abnormal pupils caused by the mitochondrial MT-TL1 gene m.3243A>G mutation - Li, Yujing; Ding, Yihong; Jin, Enzhong; Yin, Hong (Frontiers in Pediatrics, 2025)
BackgroundThe m.3243A>G mutation in the MT-TL1 gene is the most common mtDNA mutation. The mutation can lead to a spectrum of conditions, including diabetes, hearing loss, heart and muscle involvement, encephalopathy and epilepsy, gastrointestinal problems, and vision impairment, often occurring concurrently—collectively referred to as MELAS (mitochondrial encephalopathy lactic acidosis and stroke-like episodes) syndrome. Currently, it has been reported that the ocular manifestations of m.3243A>G include posterior subcapsular cataract, ptosis, extraocular muscle paralysis, and retinitis pigmentosa, among which retinitis pigmentosa is the most common ocular manifestation.MethodsThe ocular manifestations of a 10-month-old infant with mitochondrial MT-TL1 gene m.3243A>G mutation detected by genetic testing due to developmental delay were reported.ResultsOcular examination revealed Schiotz tonometry conversion values of 5.5/6 in the right eye (OD) and 5.5/4 in the left eye (OS) for intraocular pressure. Cycloplegic refraction measured +9.50 DS/−2.00 DC × 110° (OD) and +4.00 DS/−1.75 DC × 30° (OS). Anterior segment evaluation showed an irregular vertically oval pupil with absence of the temporal iris OD and a fusiform pupil OS, with no other anterior segment abnormalities detected in either eye. Fundus examination demonstrated clear optic disc boundaries bilaterally and a cup-to-disc (C/D) ratio of 0.3. Sodium fluorescein angiography revealed an intact retina without evidence of peripheral vascular leakage.ConclusionsIris defect in a infant caused by m.3243A>G mutation was reported, which complements the ocular signs of this mutation and provides a new aspect for eye screening.